Guided Wave Tomography Performance Analysis - Huthwaite,P; Lowe,M; Cawley,P (American Institute of Physics (AIP), 2015)
Quantifying wall loss caused by corrosion is a significant challenge for the petrochemical industry. Corrosion commonly occurs at pipe supports, where surface access for inspection is limited. Guided wave tomography is pursued as a solution to this: guided waves are transmitted through the region of interest from an array, and tomographic reconstruction techniques are applied to the measured signals in order to produce a map of thickness. There are many parameters in the system which can affect the performance; this paper investigates how the accuracy varies as defect width and depth, operating frequency and guided wave mode are all changed. For the S0 mode, the best performance was seen around 170kHz on the 10mm plate, with poor performance seen at almost all other frequencies. A0 showed better performance across a broad range of frequencies, with resolution improving with frequency as the wavelength reduced. However, it was shown that the resolution limit did drop relative to the wavelength, limiting the performance at high frequencies slightly.